2013
DOI: 10.1260/1747-9541.8.3.467
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Self-Modelling Video Intervention on Motor Skill Acquisition and Retention of a Novice Track Cyclist's Standing Start Performance

Abstract: The purpose of this study was to examine the effectiveness of a video-self modelling intervention on the cycling standing start performance and selfefficacy beliefs of novice track cyclists. Nineteen participants from a Talent Identification Program were randomly assigned to one of two groups (Traditional and Intervention group). The traditional group received verbal augmented feedback, whereas the intervention group received a selfmodelling video intervention in addition to verbal augmented feedback.Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Social positive reinforcement, punishment (Time out from practice) (Connelly, 1988) Increase correct execution of defensive performance Imagery rehearsal, self-talk, relaxation techniques (Kendall, Hrycaiko, Martin, & Kendall, 1990) Improve foul shooting accuracy Verbal feedback, instruction, social positive reinforcement (Kladopoulos & McComas, 2001) Teach individuals to be proficient in 9 essential basketball skills Instruction, expert modeling, forward chaining, Sr+, physical prompting (Lambert et al, 2016) Improve shot accuracy Self-imagery (Shapiro & Shapiro, 1985) Cycling Improve standing start Verbal feedback, video modeling (Jennings, Reaburn, & Rynne, 2013) Improve pressure distribution when pedaling Auditory feedback, graphical feedback (Broker, Gregor, & Schmidt, 1993) Improve pressure distribution when pedaling Auditory feedback, video feedback (Sanderson & Cavanagh, 1990) Dancing Improve ability to engage in specific competition related movements Auditory feedback (Quinn et al, 2016) Improve efficiency of three specific dance steps Instruction, self-talk (Ming & Martin, 1996) Improve execution of all "figures" Self-talk (Palmer, 1992 Self-monitoring, instruction (Rushall & Smith, 1979) Increase number of laps swam Attention, candy, and money as Sr+ (reinforcer preference assessment) (Rushall & Pettinger, 1969) Tennis and Table Tennis Improve overall serve Instruction, video modeling (Bouchard & Singer, 1998…”
Section: Discrimination Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Social positive reinforcement, punishment (Time out from practice) (Connelly, 1988) Increase correct execution of defensive performance Imagery rehearsal, self-talk, relaxation techniques (Kendall, Hrycaiko, Martin, & Kendall, 1990) Improve foul shooting accuracy Verbal feedback, instruction, social positive reinforcement (Kladopoulos & McComas, 2001) Teach individuals to be proficient in 9 essential basketball skills Instruction, expert modeling, forward chaining, Sr+, physical prompting (Lambert et al, 2016) Improve shot accuracy Self-imagery (Shapiro & Shapiro, 1985) Cycling Improve standing start Verbal feedback, video modeling (Jennings, Reaburn, & Rynne, 2013) Improve pressure distribution when pedaling Auditory feedback, graphical feedback (Broker, Gregor, & Schmidt, 1993) Improve pressure distribution when pedaling Auditory feedback, video feedback (Sanderson & Cavanagh, 1990) Dancing Improve ability to engage in specific competition related movements Auditory feedback (Quinn et al, 2016) Improve efficiency of three specific dance steps Instruction, self-talk (Ming & Martin, 1996) Improve execution of all "figures" Self-talk (Palmer, 1992 Self-monitoring, instruction (Rushall & Smith, 1979) Increase number of laps swam Attention, candy, and money as Sr+ (reinforcer preference assessment) (Rushall & Pettinger, 1969) Tennis and Table Tennis Improve overall serve Instruction, video modeling (Bouchard & Singer, 1998…”
Section: Discrimination Trainingmentioning
confidence: 99%
“…x (Hazen et al, 1990) x x x x x (Hebert & Landin, 1994) x x x x x (Hume et al, 1985) x x x (Jennings et al, 2013) x x (Kladopoulos & McComas, 2001) x x x (Continues)…”
Section: Procedural Characteristicsmentioning
confidence: 99%
“…In the studies of Whiting (1989) and Rusell (1993), VTFB was not as useful as the studies mentioned above. Jennings et al (2013) examined the effectiveness of videotape feedback on the cycling standing start performance of novice track cyclists. Nineteen subjects at the average age of 13.6 were assigned to traditional verbal feedback intervention group and video self-modelling feedback intervention group.…”
Section: Discussionmentioning
confidence: 99%
“…In the cognitive perspective, a person crosschecks on the video display to a criterion, detect errors and build corrections on the following performances. In general, researchers (Miller, & Gabbard, 1988;Haguenauer et al, 2005;Jennings, Reaburn, & Rynne, 2013) suggest that using video as a form of performance feedback can be a beneficial tool to improve motor skill learning and performance (Razali, Suwarganda, & Zawaki 2012;Barzouka, Sotiropoulos, & Kioumourtzoglou, 2015;Giannousi, Mountaki, & Kioumourtzoglou, 2017). However, research regarding VTFB is inconsistent (Tzetzis et al, 1999;Ram & McCullagh, 2003;Clark & Ste-Marie, 2007), and the impact of this seems to be related to the characteristics of the learners, with increased benefits from those more skilled in the task, or more practice with VTFB.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, researchers have investigated video-self modeling (VSM) or observation of oneself performing various sports related movements, e.g., gymnastics (Winfrey and Weeks, 1993), running (Gonzales et al, 2015), weightlifting (Franks and Maile, 1991), swimming (Dowrick and Dove, 1980), Australian Rules Football (Steel et al, 2013a,b), and cycling (Jennings et al, 2013). Unlike findings in literacy (Rao et al, 2012; Gillies, 2013), autism (Bellini et al, 2007), cerebral palsy (Dowrick, 1976) and other behavioral sciences (Dowrick, 2012), sport movement studies have indicated mixed results in support of the learning efficacy of this method (e.g., Starek and McCullagh, 1999; Law and Ste-Marie, 2005; Feltz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%